Design of a Waste Compacting Robot for Residential Use: An Advanced Study - Bruno Seixas Gomes de Almeida; Ivan Barbosa Couto Neto; Armando Carlos de Pina Filho (New Approaches in Engineering Research Vol. 10, 2021)
Nowadays, there are several robots in the market to optimize a variety of household tasks. This study aims to develop a waste compactor robot to be applied in urban residences. The type of garbage chosen was soda cans. With the present work, it was possible to specify the components of the robot systems for compacting, locomotion and electronic/control, as well as to perform its modeling and simulation. In this way, the use of the garbage compactor robots will allow garbage to arrive semi-processed in the treatment plant; a single collecting waste truck can cover a larger area; greater availability of street cleaners to work in other parts of the city; and easier to treat in landfills.